Malignant transformation rate of oral precancerous disorders to oral cancer: systematic review and meta-analysis of the current evidence - Khodadadi, Maryam; Khodadadi, Mohammadmehdi (Frontiers in Oral Health, 2025)
BackgroundOral potentially malignant disorders (OPMDs) are precancerous conditions that may eventually turn into oral cancer (OC). The aim of this present study was to reassess the data associated with OPMDs and their malignant transformation rate into oral cancer.MethodsA comprehensive search was performed in PubMed, Scopus, Embase, and Web of Science (WoS) to locate studies on OPMDs risk of OC up to July 10, 2025. A summary odds ratio (SOR) was used for the analysis of data. To explore the heterogeneity, subgroup analyses and meta-regression analyses were used. The certainty of evidence was rated using the GRADE protocol.ResultsTwenty-nine studies met the inclusion criteria. The meta-analysis showed an elevated risk of OC by overall OPMDs (SOR = 2.5 (95% CI 2.43–2.58). The highest risk of OC in OPMDs were leukoplakia (SOR = 3.35 (95% CI 3.21–3.50), erythroplakia (SOR = 3.3 (95% CI 3.21–3.50), oral epithelial dysplasia (SOR = 1.41 (95% CI 1.20–1.73), and oral submucosa fibrosis (SOR = 2.9 (95% CI 2.70–3.12). Subgroup and meta-regression analyses demonstrated a significant positive association between the development risk of OC with age and duration of follow up.ConclusionsThis study suggests a significant association between OPMDs and OC. Age and duration of follow up may modify this association. This study provides insight into the malignant transformation rate to oral cancer to aid researchers, dentists, and clinicians in efficiently controlling this disease in the general population.